Comparison of survival, acute toxicities, and dose–volume parameters between intensity‐modulated radiotherapy with or without internal target volume delineation method and three‐dimensional conformal radiotherapy in cervical cancer patients: A retrospective and propensity score‐matched analysis. (24th November 2021) - Liang, Yu‐Qin; Feng, Sen‐Quan; Xie, Wen‐Jia; Jiang, Qiong‐Zhi; Yang, Yan‐Fen; Luo, Ren; Kidd, Elizabeth A.; Zhai, Tian‐Tian; Xie, Liang‐Xi
Abstract: Background: To evaluate whether the use of the internal target volume (ITV) delineation method improves the performance of intensity‐modulated radiotherapy (IMRT) and three‐dimensional conformal radiotherapy (3DCRT) in terms of survival, acute toxicities, and dose–volume parameters. Methods: A total number of 477 cervical cancer patients who received concurrent chemoradiotherapy (CCRT) from January 2012 to December 2016 were retrospectively analyzed. They were divided into four groups: the non‐ITV (N‐ITV) + IMRT, ITV + IMRT, N‐ITV + 3DCRT, and ITV + 3DCRT groups, with 76, 41, 327, and 33 patients, respectively. Survival analysis was performed with the Kaplan–Meier and the log‐rank tests, and acute toxicity analysis was performed with the chi‐squared test and the binary logistic regression test. Using the propensity score matching (PSM) method, 92 patients were matched among the four groups, and their dose–volume parameters were assessed with the Kruskal–Wallis method. Results: The median follow‐up time was 49 months (1–119) for overall survival (OS). The 5‐year OS rate was 66.4%. The ITV delineation method was an independent prognostic factor for OS (HR [95% CI]: 0.52 [0.27, 0.98], p = 0.044) and progression‐free survival (PFS) (HR [95% CI]: 0.59 [0.36, 0.99], p = 0.045). The ITV + IMRT group had the lowest incidence rate (22%) and the N‐ITV + IMRT group had the highest incidence rate of grade ≥3 hematological toxicity (HT) (46.1%) among the four groups. The pelvic bone marrow relative V10, V20, and V30 in the N‐ITV + IMRT group was higher than those in the ITV + IMRT and N‐ITV + 3DCRT groups ( p < 0.05). Conclusions: The use of ITV for IMRT treatment planning was associated with improved overall survival and progression‐free survival, with lower HT rate. Abstract : The use of ITV for IMRT treatment planning was associated with improved overall survival and progression‐free survival, with lesser HT.